Evaluación de híbridos triliniales de maíz (Zea mays L.) en 6 ambientes de Centroamérica y El Caribe, 1989 - Pérez, Carlos (2016)
Genotype by environment interactions may modify the responseof a given cultivar acrossseveral environments. Farmer continually demand newmaize bybrids wbich respond consistently well to all production environments. With the objective of capitalizing tbe existent genetic potential in the elite lines of CIMMYT's maize hybrid program in Mexico, a collaborative bybrid project was establisbed in Central America and the, Caribbean region, where testers used are the single crosses that' are serve as females in the production of commercial hybrids by National Programs in the region. In 1988, twelve wbite and yelIow three way cross (TWC) grain hybrids were identified that had better performance across' the region and by country. In 1989, these hybrids were evaluated in uniform trials at seven locations in Central America and the Dominican Republic todetermlne tbe yield potential and adaptation of the new hybrids in maize producing areasof the region. Stability analysis was performed using the Finlay and Wilkinson model to identified the response oftbese different cultivars to the diverse environments tested. The combined analysls of 6 sites sbowed bigbly significant differences among cultivars and a significantcultivar by location interaction. The bybrid 3003x3176 (white grain) had the bigbest yield of 5.5 t/ha, representing a 37% increase over that of tbe local check, H-27. This hybrid also had the highest yield at all locations which appears to indicate a consistent response across the environments evaluated. Through this colIaborative project superior hybrids have been identified, and Panama, Costa Rica and El Salvador have commenced commercial production of certified hybrid seed. These results prove that sustainable progress can be obtained in the production of hybrids with the use of a comprehensive and dynamic system.